2021
DOI: 10.7554/elife.68424
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of subcellular actin structures with cell length through decelerated growth

Abstract: How cells tune the size of their subcellular parts to scale with cell size is a fundamental question in cell biology. Until now, most studies on the size control of organelles and other subcellular structures have focused on scaling relationships with cell volume, which can be explained by limiting pool mechanisms. Here, we uncover a distinct scaling relationship with cell length rather than volume, revealed by mathematical modeling and quantitative imaging of yeast actin cables. The extension rate of cables d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…To distinguish between the uninduced and induced cdc28-13 ts cells, we used mother cell length to sort cells into bins containing either 'small' or 'large' cells. To validate this binning strategy, we plotted the cable lengths we measured from these cells and found that the mean cable length in each bin was consistent with our previous measurements (𝐿 π‘π‘Žπ‘π‘™π‘’, π‘ π‘šπ‘Žπ‘™π‘™ = 4.1 Β± 0.3Β΅m, 𝐿 π‘π‘Žπ‘π‘™π‘’, π‘™π‘Žπ‘Ÿπ‘”π‘’ = 7.3 Β± 0.8Β΅m) (Figure 3B) (19).…”
Section: Actin Cables Taper In a Cell Length-dependent Mannersupporting
confidence: 79%
See 1 more Smart Citation
“…To distinguish between the uninduced and induced cdc28-13 ts cells, we used mother cell length to sort cells into bins containing either 'small' or 'large' cells. To validate this binning strategy, we plotted the cable lengths we measured from these cells and found that the mean cable length in each bin was consistent with our previous measurements (𝐿 π‘π‘Žπ‘π‘™π‘’, π‘ π‘šπ‘Žπ‘™π‘™ = 4.1 Β± 0.3Β΅m, 𝐿 π‘π‘Žπ‘π‘™π‘’, π‘™π‘Žπ‘Ÿπ‘”π‘’ = 7.3 Β± 0.8Β΅m) (Figure 3B) (19).…”
Section: Actin Cables Taper In a Cell Length-dependent Mannersupporting
confidence: 79%
“…To determine how extension velocity changes as a function of cell size we referred to our prior quantification of cable extension rates from temperaturesensitive cdc28-13 ts cells. At the permissive temperature, cdc28-13 ts cells are similar in size to wildtype haploid budding yeast; however, their size increases when grown at the nonpermissive temperature (19,27,28). In our prior study, we quantified cable extension rates from these enlarged cells by tracking the tips of cables marked with the fluorescent cable reporter Abp140-GFP Envy .…”
Section: Cable Extension Velocity Is Independent Of Cell Sizementioning
confidence: 99%
“…Another possible use for such a gradient could be in controlling the self-assembly of linear structures such as actin cables and flagella, which are precisely scaled to the linear dimensions of the cell ( McInally et al, 2019 ; Bauer et al, 2021 ; Datta et al, 2020 ). For example, a recent study of actin cables in yeast found that when cells were mutated to grow abnormally large, the actin cables assembled to a length that was proportional to the cell radius ( McInally et al, 2021 ). A hypothesized explanation of this phenomena is the presence of a scale-invariant gradient of depolymerizing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although extensive work has been done on S. cerevisiae actin cables ( Alioto et al, 2016 ; Chesarone et al, 2009 ; Huckaba et al, 2004 ; McInally et al, 2021 ; Miao et al, 2016 , 2013 ; Yang and Pon, 2002 ), the dynamics of Tpm1 or Tpm2 in interphase cables has not been explored in live cells. Furthermore, an extensive body of work has been done on the interplay between actin patches, actin cables and endocytosis ( Drubin et al, 2005 ; Kaksonen et al, 2005 , 2006 ).…”
Section: Discussionmentioning
confidence: 99%